Hunting Caribou : Subsistence Hunting along the Northern Edge of the Boreal Forest - Sharp, Henry S. (Book collections on Project MUSE., 2015)
"Participant ethnography of the subsistence hunting practices of a band of Denesuline in the Northwestern Territories"--